KONTRIBUSI KETERAMPILAN MEMBACA PEMAHAMAN TEKS EKSPOSISI TERHADAP KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS VIII SMP NEGERI 2 PADANG PANJANG - Liza, Ade Irma; Asri, Yasnur (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT This article reveals the contribution of skills reading comprehension text exposition to writing skills text description grade students VIII SMP Negeri Padang Panjang 2.. This research type is quantitative descriptive method. The design used in this research is the design contribution. This research population is grade VIII SMP Negeri 2 Padang Panjang are registered on the 12th school year 2018/2019, i.e. as many as 156 students. The sample in this research are determined by proportional random sampling of 25% of the population, i.e. 40 students. Research data is a score test results intermediate reading comprehension text exposition and score the writing skills test result text exposition. The data obtained through two types of tests i.e. objective tests to measure the skills of reading comprehension text exposition and performance tests to measure the skills of writing a text exposition. The results of the research there are three. First, the skills of reading comprehension text exposition grade VIII SMP Negeri Padang Panjang  2 are on good qualifications (B) by the value of the average 79.39. Second, the skills of writing text exposition grade VIII SMP Negeri Padang Panjang  2 are on good qualifications (B) with an average of 80.23. Third, there is a contribution of reading skills in the description of text to the skills of writing exposition texts of class grade VIII SMP Negeri Padang  Panjang 2 at 76,39%. Kata kunci: Kontribusi, Keterampilan, Membaca Pemahaman, Menulis, Teks Eksposisi